Alteration of the Kidney Structure of White Rat after Water Administration from Martapura River - Ida Yuliana; Lena Rosida; Husnul Khatimah; Rayatul Aminah; Alwiyah Alwiyah; Eka Amelia (Journal of Wetlands Environmental Management, 2021)
Martapura River is indicated to have been contaminated by heavy metal can adversely affect the kidneys. This study aims to analyze the impact of water consumption of the Martapura River on the microscopic image of white rat kidneys. Microscopic structure of the kidneys studied were the glomerulus, proximal renal tubule, and renal medullary tubule. Research design used a post test only with control group, with 32 white rats as the subject divided into 2 research groups, namely control group (given distilled water) and treatment group (given Martapura River water) ad libitum for 30 days. Analysis of research data using test t-independent at 95% confidence level. The results showed the number of glomerulus in the control group was less than the treatment group (p = 0.017);Â  the glomerular diameter in the treatment group was smaller than the control group (p = 0.007); the number of proximal renal tubules in the treatment group was less than the control group (p = 0.025); lumen diameter of proximal renal tubules in the treatment group was not significantly different than the control group (p = 0.025); the number of renal medullary tubules in the treatment group was not significantly different than the control group (p = 0.347); and the lumen diameter of the renal medulla tubules in the treatment did not differ significantly compared to the control group (p = 0.015). Conclusion is consuming Martapura river water which contains heavy metals causing damage to the glomerulus, proximal renal tubule and tubule of the renal medullaÂ